Project management in an aeronautical company in the state of São Paulo - Brazil - Santana, Julio Cesar Pinheiro de; Gonçales Filho, Manoel (Brazilian Journal of Production Engineering, 2021)
The level of complexity of a project requires special attention to the concepts, tools, steps and approaches that must be used to meet the client's needs. This work aims to identify projects carried out in the aeronautical industry, exploring the tools and concepts that guide the project to meet customer requirements. A second motivation is to identify theoretical models in the literature that can support the management of highly complex projects, and analyze them comparatively to the practices employed in the sector's projects. A company in the sector was investigated through an applied research, the comparative method and qualitative approach were used and the technical procedure used was the case study. The results of this research brought clarification to the practices adopted by the company, such as: the process of evaluating the real need for a project, understanding the clarity of the customer's needs plus the actions taken in subjective requirements scenarios and the interfaces that the management of requirements have with scope management. In addition to supporting the interviewees' answers by the concepts found in the literature, the results contributed to the company and the aeronautical sector understanding the phases of development and definition of verifications and validations of requirements necessary to conduct the project to meet the real needs of the customer.
Keywords: Requirements Analysis; Systems engineering; Scope Management